Birth Stories of Trinidad and Tobago Romana Peters - (:unkn) unknown (The University of the West Indies, 2024)
Romana Peters is a St. Lucian living in Trinidad and Tobago and the mother of two boys. She shares how she learned about her first pregnancy.
Keywords: Childbirth -- Trinidad and Tobago